Parents the biggest contributor to Lee Chee Ho s success - Nurul Ateeqah, Othman (2022)
KUANTAN, 17 March 2022 – “Don’t be afraid to make mistakes because mistakes ultimately lead us to success in life. “The only thing stopping us now is the way we think,” he said.